The Effect of Cone Area Variations on the Continuous Discharges Flow (CDF) Method Sedimentation Unit as a New Method for Raw Water Turbidity Removal - Ridwan Ridwan; Reri Afrianita; Aulia Massyaf Putri; Reski Anggika (Jurnal Ilmu Lingkungan, 2023)
The Sedimentation Unit Continuous Discharges Flow (CDF) method is a modification by adding a continuous and controlled discharge flow as a net force acting on the particles to increase the efficiency of turbidity removal by applying the principle of a leaky tank at the bottom of the settling zone. The production capacity of the sedimentation unit using the CDF method is reduced due to the CDF flow of 6% of the flow rate so it needs to be recirculated. This study aims to maintain the production flow rate of the system and increase the efficiency of turbidity removal by recirculating the CDF flow. The research reactor consisted of a coagulation unit, flocculation unit, and sedimentation method using 6% CDF with a flow rate of 240 L/hour and 360 L/hour, and variations in the recirculation flow of 6% CDF to the flocculation unit were 0%, 25%, 50%, 75%, and 100 %. The sedimentation detention time at a flow rate of 240 L/hour and 360 L/hour was 90 minutes and 60 minutes, respectively. Research on a laboratory scale with raw water turbidity of 25,536 NTU. The results showed that the greater the CDF flow recirculation value, the higher the turbidity removal efficiency. Rank Spearman analysis, the correlation value of the CDF flow recirculation value to the efficiency of removal of turbidity is 0.980 and the significance value is 0.00 which means strong and significant. The highest turbidity removal efficiency was achieved at the 100% CDF flow recirculation value, ie at 240 L/hour flow rate was 87.21% with final turbidity 3.267 NTU, while at 360 L/hour flow rate was 82.50% with final turbidity 4,528 NTU. Uprating the flow rate in the experiment was able to produce a final turbidity value that met the drinking water quality standard, which was 5 NTU